Avaliação de critérios de estabilidade do processo MIG/MAG curto-circuito na soldagem de aços inoxidáveis austenítico e duplex - Costa, Thonson Ferreira (2014)
Stability of welding processes is fundamental to accomplish weld beads with good quality. Such stability can be defined by the regularity of metal transfer, as well as spattering generation and final bead quality. During short-circuit transfer, the process stability is straight affected by periodic arc extinction, which is generated by the contact of metal droplet at wire tip with the weld pool. This feature leads to spattering increase, which reduces the process productivity by losing filler material or by increasing costs with spattering removal out of the workpiece, and also affects the bead quality. In addition, the regularity of short-circuit transfer is related to low variation of parameters, such as short-circuit time, open arc time and peak current. Therefore, it is proposed to unprecedentedly assess the regularity of short-circuit transfer during conventional MIG/MAG welding of austenitic and duplex stainless steels and correlates to spattering generation, deposition rate, surface bead quality, bead geometrical features and thermal efficiency. The reference voltage was varied between 14 and 22 V, wire feed speed between 2,8 and 3,8 m/min and the contact-tip to workpiece distance was varied to achieve two current levels (125 ± 5 A e 155 ± 5 A) for two shielding gases (Ar+2%O2 e Ar+2%CO2). Weldments were carried out on plates made of AISI/UNS 304L austenitic stainless steel AISI/UNS S31803 (SAF 2205) and duplex one, both with 4,5 mm thickness. Spattering generation analyses were carried out by using square bars with 3/8 made of AISI 304L austenitic stainless steel with 250 mm of length. AWS ER308LSi and AWS ER2209 filler wires with 1,2 mm of diameter were used for austenitic and duplex stainless steels weldments, respectively. The results indicated there is a suitable voltage range between 15 a 19 V, which allows an appropriate short-circuit transfer. Within this range is possible to achieve better metal transfer regularity, low spattering level, high deposition rate and best bead quality. Moreover, it ratifies the correlation among the different employed methods to determine the metal transfer regularity. On the other hand, thermal efficiency analyses did not show a clear correlation to metal transfer regularity.